Bioethics a Christian approach in a pluralistic age - Rae, Scott B.; Cox, Paul (Grand Rapids, MI Eerdmans, 1999)
Includes bibliographical references and index.
Keywords: Medical ethics; Christian ethics; Medicine -- religious aspects -- Christianity